IMPACT OF GENDER, AGE AND RANK ON JOB SATISFACTION IN BANGLADESH PERSPECTIVE - Mohammad Moinul Haque; Fazlul Kabir Rabbanee (Indonesian Management and Accounting Research, 2007)
Job satisfaction is a pleasant state of mind of an employee derived from his or her job experience. It depends on what one expects and what he or she receives. This study is to explore the impact of gender, age and rank on job satisfaction in organizations operating in Bangladesh. 255 valid responses were collected on random basis from respondents of different organizations on four questions. It was found that most of the employees in Bangladesh were satisfied with their job. It was also found that neither gender by itself, nor when it was considered with age nor when it was considered with rank nor when it was considered with age and rank together, had any statistical significant effect on determination of job satisfaction. However, age and rank either individually or jointly, were found having statistically significant impact on job satisfaction. Keywords: Job Satisfaction, Gender, Rank, and Age.